Pengaruh Model Pembelajaran Berbasis Masalah pada Kemampuan Literasi Ilmiah Siswa dalam Materi Transfer Panas Kelas V di Sekolah Dasar - Khilda Audina; Arie Widya Murni; Novaria Lailatul Jannah; Hikmah Luqiyah Kartikasari (DIDAKTIKA, 2024)
Thesis This aim For know influence of learning models based problem to ability literacy participant educate on the material displacement heat fifth grade school base . As for the background study This based on results interviews and observations carried out , where ability literacy science participant still studying in class V spelled out low as well as lack of understanding teacher towards various various learning models . Study This carried out at SDN Banjarkemantren 2 in the even semester year 2022/2023 teachings . Method research used _ is Pre Experimental Design with One Group Pretest-Posttest Design type . Sample in study is participant educate VA class totaling 31 participants educate . Instruments used _ form instrument test form question choice double as well as sheet observation teacher and participant activities students , data obtained from test choice double and observation related with ability literacy science . Data analysis used the normality test and t-test. Analysis results show that the data is normally distributed because sig value . > 0.05 and in the t- test with using paired sample t-test results sig value <0.05 at level significance 5% then can it is concluded that h0 is rejected and ha is accepted . This matter show that application of learning models based problem give influence to ability literacy science participant educate on the material displacement heat in class V school base